Pengaruh Tangible, Reliability, Responsiveness, Assurance Dan Emphaty Terhadap Kepuasan Nasabah Bank Jabar Banten Di Surabaya - Thyophoida W.S. Panjaitan (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
If the banks want to continue to exist it is necessary to create a business concept that is still running. One of the concepts in these activities is the concept of marketing. Success or failure of business activities depends on how the marketing system, so it is important for banks to understand the "why" and "how" of consumer behavior is so, so it can develop, promote, and distribute their products better than competitors. Customer satisfaction is strongly influenced by the quality of services provided. The factors that used effects the service quality customer satisfaction in Bank Jabar Banten include: Reliability, Responsiveness, Assurance, Emphaty, and Tangible. This study aims to find out the influence of Reliability, Responsiveness, Assurance, Emphaty, and Tangible simultaneously and partially on customer satisfaction with the Bank Jabar Banten. The results support the hypothesis that states there is an influence factors simultas Reliability,Responsiveness, Assurance, Emphaty, and Tangible customer satisfaction where the value of F test of 29.562 and a significant level of 0.00 is smaller than the significant level was set at 0, 05. From the results of t test is known that assurance and that signifika tangible influence on customer satisfaction, while the Reliability, Responsiveness, and emphaty no effect on customer satisfaction. From the results of t test is also known tangible have t test value of 5.085 so that can be said to have the most dominant influence on customer satisfaction in Bank Jabar Banten in Surabaya.